Promoting ownership in a “post‐aid effectiveness” world: Evidence from Rwanda and Liberia - Keijzer, Niels; Klingebiel, Stephan; Scholtes, Fabian (Development policy review, 2020)
Motivation After generating considerable momentum in the period 2005–2011, policy debates on the aid effectiveness agenda—including the core principle of ownership—witnessed a sharp decline. Current trends raise questions about the continuing relevance of ownership as a fundamental principle for development co‐operation. Purpose This article analyses how approaches to managing development co‐operation have evolved in Rwanda and Liberia, two aid‐dependent post‐conflict states that were previously at the forefront of the aid effectiveness agenda. It presents new evidence on how ownership features and is promoted in development co‐operation relations. Approach and Methods The article draws on 48 semi‐structured interviews, complemented by a review of academic literature, policy documents and grey sources concerning the two countries and the broader subject matter. Findings Recent years have shown considerable drift in Liberia’s approach to development co‐operation management, while Rwanda retained its established system to manage its external partnerships and incentivize donor behaviour. Both cases illustrate challenges in promoting ownership among all relevant stakeholders, with a key shift being that donors increasingly favour the “what” of co‐operation over the “how.” Policy implications In view of the importance of ownership for the sustainability of development co‐operation, policy‐makers should consider reinvigorating and repositioning a self‐standing development effectiveness agenda. Such an international initiative should adjust to new co‐operation trends, notably the increased practice of predetermining co‐operation themes and the promotion of multi‐stakeholder approaches.